STRATEGIES AND PROSPECTS FOR ENERGY SECURITY OF KAZAKHSTAN IN THE XXI-st CENTURY - Nauanova K.M.,Imasheva M.M.,Kisseleva Darya (Вестник ЗКУ, 2026)
The foundation of the energy security of the Republic of Kazakhstan is the resilience of its energy system, which ensures reliable energy supply under conditions of technological change and external challenges. In this context, the article examines the key directions of transformation of Kazakhstan’s energy sector, including the development of renewable energy sources, the condition of power grid infrastructure, and the prospects for the introduction of nuclear energy. The analysis is based on a synthesis of regulatory and legal documents, energy development strategies, and data on the current state of the country’s energy complex.The analysis shows that Kazakhstan’s energy system is characterized by a high share of carbon-based generation, significant wear of grid infrastructure, and limited capacity of renewable energy sources to provide baseload power. As a result of the study, the necessity of diversifying the energy balance, modernizing infrastructure, and expanding the use of renewable energy sources is substantiated as key factors for enhancing Kazakhstan’s energy resilience. It is established that wind and solar energy contribute to the diversification of electricity generation; however, they require grid modernization and the implementation of balancing mechanisms. Under these conditions, nuclear energy is considered a factor that can enhance the resilience of the energy system, reduce dependence on cross-border electricity flows, and strengthen the country’s energy security in the long term.